CANINE PARVOVIRUS ENTERITIS INFECTION IN LOCAL DOGS IN SAMPLANGAN VILLAGE, GIANYAR REGENCY, BALI - Anjani, Fauzia Hadista; Suardana, Ida Bagus Kade; Suarjana, I Gusti Ketut; Winaya, Ida Bagus Oka; Apsari, Ida Ayu Pasti (Buletin Veteriner Udayana, 2025)
A common disease that poses a threat to dogs is Canine Parvovirus (CPV). Puppies tend to be more susceptible to CPV infection due to a period called the window of susceptibility. The purpose of this case study is to determine clinical changes that include anatomical pathology, histopathology, and laboratory examinations to establish a definitive diagnosis of the case animal. The animal used in the case study was a four-month-old female local puppy from Gianyar, Bali. The case dog was found freshly dead, and had been sick for 4 days. The dog showed symptoms of weakness, anorexia, and vomiting, bloody diarrhea. Polymerase Chain Reaction (PCR) test results were positive for Canine Parvovirus infection. Anatomical pathology changes found were congestion of the brain, hemorrhage of the trachea, swelling of the heart, hemorrhage of the liver, hemorrhage of the patu-peru, hyperemia of the renal medulla, blackening and swelling of the spleen, hemorrhage of the intestines, and bleeding of the stomach. Histopathological changes observed were tracheitis, necrotizing bronchopneumonia, myocarditis, hemorrhagic glomerulo-nephritis, speinitis, gastritis, and necrotizing enteritis. Based on clinical symptoms, anatomical and histopathological pathology observations, and Polymerase Chain Reaction (PCR) results, it can be concluded that the case dog was infected with Canine Parvovirus type enteritis. It is necessary to vaccinate dogs and pay attention to environmental cleanliness to minimize the transmission of Canine Parvovirus infection.